1999
DOI: 10.1111/1467-8454.00049
|View full text |Cite
|
Sign up to set email alerts
|

Export‐led Growth and Import Compression: Further Time Series Evidence From LDCs

Abstract: This paper conducts tests of the export-led growth and the import-compression hypotheses for four less developed countries (LDCs) ± India, Nigeria, Fiji and Papua New Guinea (PNG). Based on Johansen's multiple cointegration test preceded by unit root tests, we test for cointegration between real output, exports and imports. Non-rejection of cointegration between the variables excludes the possibility of Granger non-causality and suggests at least one way Granger causality. Real output, exports and imports are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Subsequently, a number of studies have adopted this revised methodology (Marin, 1992;Dutt and Ghosh, 1996;Rahman and Mustafa, 1997;Islam, 1998;Ekanayake, 1999;Anoruo and Ramchander, 2000;Chandra, 2004 and2005;Thangavelu and Rajaguru, 2004). Furthermore, of particular significance, several previous studies adopt a multivariate approach using import growth as an additional explanatory variable (Riezman et al, 1996;Asafu-Adjaye and Chakraborty, 1999;Thangavelu and Rajaguru, 2004). Hence, it is within this established body of literature that our study is located.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Subsequently, a number of studies have adopted this revised methodology (Marin, 1992;Dutt and Ghosh, 1996;Rahman and Mustafa, 1997;Islam, 1998;Ekanayake, 1999;Anoruo and Ramchander, 2000;Chandra, 2004 and2005;Thangavelu and Rajaguru, 2004). Furthermore, of particular significance, several previous studies adopt a multivariate approach using import growth as an additional explanatory variable (Riezman et al, 1996;Asafu-Adjaye and Chakraborty, 1999;Thangavelu and Rajaguru, 2004). Hence, it is within this established body of literature that our study is located.…”
Section: Literature Reviewmentioning
confidence: 97%
“…This is potentially significant since the import-led growth hypothesis indicates that export growth relieves the foreign exchange constraint, allowing capital and intermediate inputs to be imported to boost domestic production (Asafu-Adjaye and Chakraborty, 1999). Indeed, a number of previous studies (Riezman et al, 1996;Asafu-Adjaye and Chakraborty, 1999;Thangavelu and Rajaguru, 2004) include imports as an additional variable when examining the causal relationship between exports and economic growth whereby failure to account for its role could produce misleading results in the analysis of the relationship between export growth and output growth. Thirdly, this paper seeks to investigate the causality between both real exports and real imports in relation to real GDP using more recent techniques in terms of Johansen's multivariate cointegration framework.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, results from previous studies varies between in-favour and not in-favour of four main hypotheses: Export-Led Growth (ELG), Growth-Led Export (GLE), Import-Led Growth (ILG) and Growth-Led Import (GLI). More specifically, many empirical studies argue that export growth and openness to foreign countries is an important determinate of economic growth (see, Awokuse 2007;Asafu-Adjaye and Chakraborty 1999). However, empirical support for GLE hypothesis is relatively stronger (Ghartey 1993;Kubo 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Levine and Renelt (1992), and Wacziarg (2001) found that the major channel for trade and growth is investment. In line with that idea, recent timeseries literature found that the causality going from exports to output growth is stronger than that going vice versa (see Riezman et al, 1996;Islam, 1998;Asafu-Adjaye and Chakraborty, 1999;Krishna et al, 2003).…”
Section: Introductionmentioning
confidence: 71%